ANALISA DENSITAS DAN FREE WATER SEMEN PEMBORAN BERDASARKAN KONSENTRASI ADITIF BERBAHAN DASAR GLUKOSA - Hastowo Resesiyanto (INTAN Jurnal Penelitian Tambang, 2021)
Cementing is the process of placing the cement suspension into the casing, then it will come out through the bottom of the casing shoe and will flow up into the space between the casing and the formation. In making cement suspension, the properties of the cement must be considered because it will affect the quality of the cement results. This study aims to examine changes in density and free water content of cement suspension as a result of the addition of glucose-based additives. Meanwhile, testing of other drilling cement properties was not carried out. Based on the results of the study showed that the more concentration of additives added to the cement suspension, the cement density value will increase. This will affect the hydrostatic pressure of the drilling cement in the borehole later. Meanwhile, for free water testing, values ​​tend to be stable ranging from 3 – 3.2 cc or 1.2 – 1.28% or below what is allowed.